Pengaruh Produksi, Harga Internasional, dan Nilai Tukar Rupiah Terhadap Ekspor Kakao di Indonesia Periode Tahun 2012-2021 - Niza Utami; Nurlaila Nurlaila; Reni Ria Armayani (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2023)
Indonesia is a developing country with an abundance of natural resources. This abundant natural resource wealth is a distinct advantage for Indonesia, this natural wealth produces a variety of commodities that can become a source of state revenue by trading them. The purpose of this study was to determine the effect of cocoa production, international cocoa prices, and the rupiah exchange rate on the value of cocoa exports in Indonesia. The data used in this research is secondary data. Data sources were obtained from various institutions such as the Central Statistics Agency, Bank Indonesia, World Bank, Ministry of Agriculture, International Cocoa Organization and other sources related to this research. This research is explanatory research in nature. In this research, a quantitative approach was used. The data analysis technique uses multiple linear regression tests. The results of the study, namely, cocoa production has no significant effect on the value of cocoa exports in Indonesia. International prices have a significant effect on the value of cocoa exports in Indonesia. The rupiah exchange rate has a significant effect on the value of cocoa exports in Indonesia. Keywords: Production, Internasional Prices, Rupiah Exchange Rate